Attributes of a Mobile App as Perceived by Field Veterinarians: Case of Pig Master (Indian Journal of Extension Education, 2023)
his study presents the perceived characteristics of pig master, a mobile app developed as a Continuing Veterinary Education (CVE) tool for veterinarians. The CVE programmes are being taken up by various institutions in India and it was observed that many of the field veterinarians are not able to attend the regular CVE programmes for obvious reasons, for whom ICT tools like mobile devices can be useful. In this context, veterinarians’ perception of the mobile application on pig farming developed after the need assessment was assessed. The study was carried out with the veterinarians of the State Department of Animal Husbandry (SDAH), Andhra Pradesh. A sample of 91 field veterinarians was studied to whom Android Package on pig farming and questionnaires were sent. The ‘pig master’ mobile application was found to have good visual quality, more credible, effective in arousal of curiosity and was with high information coverage along with user-friendliness. Moreover, the app was also found with remarkable utility and helpful in decision-making as expressed by the majority of the field veterinarians. This study emphasizes the need of making CVE programmes effective by using digital media towards enrichment of knowledge of veterinarians.